Long-term risk of irritable bowel syndrome associated with MASLD, MASLD type and different cardiometabolic risk factors: a large-scale prospective cohort study - Yesheng Zhou; Zhirong Yang; Si Liu; Sian Xie; Qian Zhang; Shutian Zhang; Shengtao Zhu; Shanshan Wu (BMC Gastroenterology)
Abstract Background Despite the increased irritable bowel syndrome (IBS) risk associated with hepatic steatosis demonstrated in prior evidence, it is still unclear whether the newly coined metabolic dysfunction-associated steatotic liver disease (MASLD), could in reverse impact IBS development. We prospectively assessed the association of MASLD, MASLD type and different cardiometabolic risk factors (CMRFs) with incident IBS in a nationwide population-based cohort. Methods Participants free of IBS at baseline in UK Biobank were included (N = 380,619). MASLD, MASLD type [pure MASLD, MASLD with increased alcohol intake (MetALD)] and CMRFs were defined based on the new criteria in America and Europe. Cox proportional hazard model was used to assess the associated risk of incident IBS. Results Overall, 143,857 (37.8%) had MASLD at baseline. During a median 13.2-year follow-up, 7329 incident IBS cases were identified. Compared with normal individuals, MASLD patients had an 11% elevated risk of IBS (HR = 1.11, 95%CI: 1.04–1.20). The increased risk was present in both pure MASLD (HR = 1.12, 1.03–1.21) and MetALD (HR = 1.26, 1.09–1.45) patients. Moreover, a substantially greater risk of IBS was observed as the number of CMRFs increased in MASLD patients (P trend < 0.001), with 16% and 30% higher risk in MASLD with 3 CMRFs (HR = 1.16, 1.06–1.27) and ≥ 4 CMRFs (HR = 1.30, 1.17–1.43) patients. Additionally, risk of IBS was significantly higher among MASLD patients with a certain CMRF [overweight/obesity (HR = 1.14, 1.05–1.23), dysglycemia (HR = 1.15, 1.05–1.27) and dyslipidemia (HR = 1.18, 1.09–1.28)] versus normal individuals, respectively. Further sensitivity analysis and subgroup analysis indicated similar results. Conclusions MASLD, either pure MASLD or MetALD, was associated with an increased risk of incident IBS, with greater risk with more cardiometabolic risk factors, suggesting management of MASLD may help prevent IBS.